On the modal acoustic emission testing of composite structure. (15th April 2016) - Dahmene, F.; Yaacoubi, S.; El Mountassir, M.; Bendaoud, N.; Langlois, C.; Bardoux, O.
Abstract: This paper concerns the use of Modal Acoustic Emission (MAE) on composite overwrapped pressure vessels (COPV). It investigates the physics of this approach, defined as a promising method that can provide further information to classical acoustic emission technique. The investigations are achieved on a small coupon and full scale specimens extracted from a COPV. The separation mode was previously performed using Pencil Lead Breaks (PLBs) based on Continuous Wavelet Transform (CWT) analysis. It has been shown that extensional (S0 ) and flexural (A0 ) modes were successfully splitted and their frequency bandwidths are defined. After that, an appropriate algorithm was developed based on CWT analysis of the extracted AE signals coming from the region of damage. Results obtained by this method show a good agreement regarding the nature of damage and predominant mode expected during tensile test.